2016
DOI: 10.1590/1678-4162-8682
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of water use and nitrogen for goat milk production in irrigated pasture to different management

Abstract: The aim was to determine the efficiency of use of water and nitrogen for forage production and goat-milk production on an irrigated Tanzania Guineagrass (Panicum maximum cv. Tanzânia) pasture subjected to different management practices. The management levels tested were combinations among nitrogen fertilization levels and post-grazing residual heights (ResH): Intensive (ResH = 33.0cm and 600.0kg N/ha.year-1); Moderate (ResH = 47.0cm and 300.0kg N/ha.year-1); Light (ResH = 47cm and 0kg N/ha.year-1); and Convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The greater the plant evapotranspiration, the lower water content the plant can utilize. Our findings are therefore consistent with those of several other studies (Varnamkhasti et al, 1995;Xu et al, 1998;Cavalcante et al, 2016). There was a negative correlation between WUE and soil bulk density.…”
Section: Adaptation Of Water Use Efficiency Of Alpine Meadow Ecosystem To Environmental Factorssupporting
confidence: 94%
See 2 more Smart Citations
“…The greater the plant evapotranspiration, the lower water content the plant can utilize. Our findings are therefore consistent with those of several other studies (Varnamkhasti et al, 1995;Xu et al, 1998;Cavalcante et al, 2016). There was a negative correlation between WUE and soil bulk density.…”
Section: Adaptation Of Water Use Efficiency Of Alpine Meadow Ecosystem To Environmental Factorssupporting
confidence: 94%
“…However, our experimental results show that for all the dominant, coexisting, and functional group species, the WUE of plants was the highest under moderate grazing treatment, and grazing activities increased the WUE of plants. Similar results by Cavalcante et al (2016) revealed that moderate grazing increased WUE by 37.72% compared to traditional grazing. In Inner Mongolia, the typical grassland community WUE was highest under moderate grazing (Lv, 2016), which was increased by 62.86% compared to no grazing.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation